Whose city is it anyway? – Contested Citizenship in Karachi - Mirbahar, Hassan Nasir (Muslim Politics Review, 2024)
Karachi, a city of migrants, is a socially and politically polarized metropolis. Thus, it is mired with inter-ethnic conflicts. Each group claims their right to the city is superior to others’. Muhajirs claim that they made sacrifices for the creation of Pakistan and make up the majority; hence, they have more rights over the city than others. Sindhis see themselves as the Indigenous population, as they founded the port city, while Pashtuns and Punjabis suggest they brought much of the capital that fuels the city’s economy. These diverging claims result in the contestation over both city and citizenship in the city. This contested citizenship intersects with power politics in Karachi, marked by extreme violence and ethnic hatred. This paper evaluates the nature of contested citizenship against historical developments in Karachi. It argues that the divergent paths of each ethnic group, leading to same city, have created multiple competing claims on the city, resulting in one group cancelling the claims of the others. Ultimately, citizenship itself has become contested.